Kinematic analysis of some biomechanical variables and their relationship with accuracy index and spike performance speed in national volleyball team players - Heidi, Dr. Heidi Qasim Baiz; Yasser, Prof.Dr. Yasser Najah Hussein; Hamid, Prof.Dr. Huda Hamid Abdul Hussein; Gamal, Asst.L. Ahmed Gamal Fathallah (Sulaimani Journal for Humanities, 2025)
The research problem was summarized in several questions: Is it possible to benefit from analyzing some offensive skills, their accuracy and speed in volleyball mechanically, and what are the correlations of the biomechanical variables with the accuracy and speed of the crushing strike to achieve the highest level reached by the player? The research aimed to identify the values of some biomechanical variables and their values. Accuracy and speed of volleyball offensive skills, and identifying the relationship between them. The descriptive approach was used using the survey method to study correlational relationships for the research sample, which consisted of 12 elite players, and was extracted by performing a crushing multiplication test, in addition to using two cameras (120 images/second) and a foot scan device. The results showed that there were correlations in the preparatory stage between the variables of accuracy and speed of the crushing strike with the time of support and the angle of the knee joint at the moment of pushing and the time of pushing, as well as the presence of correlations in the main stage between each of the variables of accuracy and speed of the crushing strike with the time of flight and the height of the starting point of the ball at the moment. beating.